Corrigendum to ‘Quantification of the exposure of consumers and hairdressers to formaldehyde and oxalic acid after application of hair straightening products containing glyoxylic acid’ [Toxicol. Appl. Pharmacol. 515 (2026) 117940] - Nicola J. Hewitt; Carsten Goebel; Jens Diller; Anne Fuchs; Rolf Fautz; Brunhilde Blömeke; Katharina Schwarz; Shimpei Terasaka; Kazutoshi Saito; Rebecca Justiniano; Gábor von Bölcsházy (Toxicology and Applied Pharmacology, 2026)

Quantification of the exposure of consumers and hairdressers to formaldehyde and oxalic acid after application of hair straightening products containing glyoxylic acid - Nicola J. Hewitt; Carsten Goebel; Jens Diller; Anne Fuchs; Rolf Fautz; Brunhilde Blömeke; Katharina Schwarz; Shimpei Terasaka; Kazutoshi Saito; Rebecca Justiniano; Gábor von Bölcsházy (Toxicology and Applied Pharmacology, 2026)

Corrigendum to ‘Quantification of the exposure of consumers and hairdressers to formaldehyde and oxalic acid after application of hair straightening products containing glyoxylic acid’ [Toxicol. Appl. Pharmacol. 515 (2026) 117940] - Nicola J. Hewitt; Carsten Goebel; Jens Diller; Anne Fuchs; Rolf Fautz; Brunhilde Blömeke; Katharina Schwarz; Shimpei Terasaka; Kazutoshi Saito; Rebecca Justiniano; Gábor von Bölcsházy (Toxicology and Applied Pharmacology, 2026)

Conservation implications of low contemporary connectivity along the Mid‐Atlantic Ridge in hydrothermal vent gastropods - E. Portanier; A. Tran Lu Y; F. Pradillon; C. Daguin‐Thiébaut; S. Ruault; P. Collins; E. Omnes; S. Fuchs; J. Carlsson; D. Jollivet; M. Matabos (Conservation Biology, 2026)
Polymetallic sulfide deposits produced at hydrothermal vent fields are targets for mining exploitation along the Mid‐Atlantic Ridge, threatening the functioning and resilience of vent ecosystems that provide multiple ecosystem services. Knowledge about connectivity between vents will inform conservation practices. The present‐day genetic structure and demographic history of the two vent‐dwelling gastropod species, Lepetodrilus atlanticus and Peltospira smaragdina , were investigated using more than 15,000 single‐nucleotide polymorphisms and mt Cox1 sequences. Each species comprised three genetic groups. Genetic breaks were stronger for L. atlanticus , separating three distinct operational taxonomic units (5°S, Broken Spur at 29°N, and the Azorean vent fields near 37°N). Peltospira smaragdina was also geographically separated into three groups: Broken Spur, TAG, and Snake Pit (23–29°N); Lucky Strike (37°N); and Moytirra (45°N). A semipermeable zone was detected south of Rainbow (35°N), similar to that of vent mussels in this area, suggesting the presence of a multispecies hybrid zone. Demographic inferences supported secondary contact between most pairs of metapopulations for both species, but the time since contact was insufficient for allele frequencies to rehomogenize. Gene flow between vent fields may be sporadic and rare or restricted by genetic barriers. The fragmentation of species into isolated metapopulations may reduce their resilience to disturbance and create the need for specific conservation measures. Isolated populations (e.g., Moytirra for P. smaragdina , 5°S and Broken Spur for L. atlanticus ), source populations (e.g., Lucky Strike for P. smaragdina ), admixture areas, and sites that may act as stepping stones within a metapopulation must be protected from deep‐sea mining. An average distance of

The ongoing journey of modelling intercropping systems: A conceptual resource sharing intercomparison from model developers and expert users - Adam Muhammad Adam; Myriam Adam; Folkard Asch; Kenneth J Boote; Vimbayi Grace Petrova Chimonyo; Mathias Christina; Marc Corbeels; Antoine Couëdel; Mathilde De Freitas; Tomas Della Chiesa; Frank Ewert; Gatien N Falconnier; et al. (Field Crops Research, 2026)

The grapevine Vitis shuttleworthii accession D’Arpa reveals resistance against Xiphinema index in an inoculation screening assay - F. Fuchs; J. Schurig; M. Nicklas; A. Baßler; O. Trapp; P. Winterhagen (European Journal of Plant Pathology, 2026)
The Grapevine fanleaf virus (GFLV) transmitted by the vector nematode Xiphinema index causes severe losses in viticulture. Truly resistant rootstocks that inhibit nematode development and virus transmission to grapevines are not available. Seedlings with genetic background of the accession Vitis shuttleworthii D’Arpa were evaluated using an established screening system to test for nematode resistance. For all tested candidate grapevines it turned out that reproduction and fertility of X. index was strongly reduced compared to the susceptible control rootstock Selektion Oppenheim (SO4) and similar to the partly resistant reference rootstock Nemadex Alain Bouquet. GFLV infection was identified on controls and references after inoculation with viruliferous nematodes, but virus was not detected in any of the candidate genotypes with D’Arpa background. Results indicate that D’Arpa contains resistance traits, which may be interesting for breeding nematode resistant rootstocks.

Quaternary terrace formation in response to climate, regional uplift and local normal faulting: The Danube terrace staircase of Vienna - B.C. Salcher; S.M. Neuhuber; J.-C. Otto; T. Payer; C. Lüthgens; S. Fuchs; A. Flores-Orozco; J. Nørgaard; S. Grupe; O. Marchhart; A. Wieser; J. Lachner; et al. (Quaternary Science Reviews, 2026)

Suitability of the use of the intraperitoneal route in the in vivo micronucleus test to evaluate the genotoxicity of hair dyes - Nicola J. Hewitt; Hind Assaf Vandecasteele; Paul Benndorf; Rolf Fautz; Anne Fuchs; Karma Fussell; Carsten Goebel; Torben König; Fabrice Nesslany; Juliane Werner; Paul Fowler (Regulatory Toxicology and Pharmacology, 2026)

Correction: Seasonal and Interannual Variability of Exchange between Delaware Bay and the Continental Shelf - Gregory P. Gerbi; Elias J. Hunter; Jacqueline M. McSweeney; Heidi L. Fuchs; Robert J. Chant; Jessica C. Garwood; John Wilkin (Estuaries and Coasts, 2026)

Seasonal and Interannual Variability of Exchange Between Delaware Bay and the Continental Shelf - Gregory P. Gerbi; Elias J. Hunter; Jacqueline M. McSweeney; Heidi L. Fuchs; Robert J. Chant; Jessica C. Garwood; John Wilkin (Estuaries and Coasts, 2026)
This study of Delaware Bay, USA, uses a numerical particle tracking model to examine the exchange of material between the bay and adjacent continental shelf on seasonal timescales. Vertically averaged, near-bottom, and near-surface transport were targeted by simulating particles with three different types of behavior: neutrally buoyant, bottom-seeking (similar to silt settling), and surface-seeking (similar to the slow rise of buoyant material), respectively. Particle release locations are drawn from a space-filling distribution throughout the model domain, and the origin regions of particles that enter the bay vary seasonally, interannually, and with particle behavior. The mean along-shelf circulation is from the northeast to the southwest, and particles entering the bay tend to come from the northeast, within tens of kilometers from shore. Source regions of bottom-seeking particles that enter the bay are farther offshore than source regions of neutral or surface-seeking particles. Bottom-seeking particles also remain in the bay for longer times than particles with other behaviors. Particles of all behaviors are flushed out of Delaware Bay more quickly in winter than in summer. Although this study focuses on a specific region of eastern North America, the findings about sources of particles to the bay are likely applicable to other embayments with similar shelf circulation patterns and may guide efforts to better understand transport of pollutants, larvae, and other material.

No Refuge at the Edge for European Beech as Climate Warming Disproportionately Reduces Masting at Colder Margins - Jessie J. Foest; Jakub Szymkowiak; Marcin K. Dyderski; Szymon Jastrzębowski; Hanna Fuchs; Ewelina Ratajczak; Andrew Hacket‐Pain; Michał Bogdziewicz (Ecology Letters, 2025)
Reproduction is vital for forest resilience under climate change, enabling tree populations to recover from disturbances and migrate. Yet projections of habitat suitability often overlook seed production. For European beech ( Fagus sylvatica ), viable seed production depends on year‐to‐year variability and synchrony in reproduction (masting). Using data from 341 sites (mean record: 31.7 years), we show that, especially in colder sites, increased frequency of the main reproductive cue is linked to strong declines in masting (CVp decline up to ~54%). This suggests that high latitudes and elevations offer no refuge, countering common assumptions and trends in other demographic processes. Severe disruptions to masting are projected to become the norm, with the greatest reductions (up to ~83%) at colder margins. Masting disruption may threaten forest regeneration and have far‐reaching ecological impacts. Monitoring recruitment and testing adaptive forest management in vulnerable areas will be essential to mitigate reproductive constraints on forest resilience.

Human endothelial colony forming cells (ECFCs) require endothelial protein C receptor (EPCR) for cell cycle progression and angiogenic activity - Sarah E. J. Chambers; Jasenka Guduric-Fuchs; Edoardo Pedrini; Pietro M. Bertelli; Chutima Charoensuk; Elisa Peixoto; Varun Pathak; Hamza I. Alhamdan; Ruoxiao Xie; Anna Krasnodembskaya; Judith Lechner; Alan W. Stitt; et al. (Angiogenesis, 2025)
Vascular repair and regeneration are critical for tissue homeostasis. Endothelial colony forming cells (ECFCs) are vessel-resident progenitors with vasoreparative capacity and they offer an important avenue for allogeneic cytotherapy to achieve perfusion of ischemic tissues. Endothelial Protein C Receptor (EPCR) has been proposed as a marker for vascular endothelial stem cells, but its precise role in ECFC biology remains unknown. The current study has investigated the biological relevance of EPCR in ECFC function. Our data show that over 95% of ECFCs exhibit high EPCR expression. These levels surpassing CD34 and CD157, positions EPCR as a new robust ECFC immunophenotypic marker, alongside established markers CD31 and CD105. Functionally, depleting EPCR expression in ECFCs significantly diminished angiogenic activity, including proliferation, migration and tube formation. This knockdown also altered normal ECFC barrier function. Transcriptomic analysis indicated that knockdown of EPCR led to enrichment of gene signatures for cell cycle, TGF beta, and focal adhesion kinases. G1 cell cycle arrest was confirmed in ECFCs with depleted EPCR. Mechanistically, EPCR knockdown led to increased release of TGFβ2 and SMAD2/3 activation, coupled with increased p21, decreased pFAK, and increased transgelin. Additionally, we showed that quiescent ECFCs showed significantly lower EPCR expression when compared to proliferating ECFCs. In agreement with this, cell sorting experiments demonstrated that ECFCs with the highest EPCR expression exhibited the highest clonogenic capacity. In summary, our findings highlight that EPCR expression in ECFCs is critical for their angiogenic activity, by modulating cell cycle progression. Graphical abstract

Contrasting Population Trajectories of Temperate Reef Fishes and Invertebrates Following Seasonal and Multi‐Decadal Temperature Change - Yann Herrera Fuchs; Graham J. Edgar; Neville S. Barrett; Lara Denis‐Roy; Shenae Y. Willis; Hunter Forbes; Rick D. Stuart‐Smith (Global Change Biology, 2025)
Temperature perturbations from climate change affect ecosystems through short‐term pulse events, such as heatwaves, and chronic long‐term shifts. Temperate rocky reef ecosystems have been observed to show substantial ecological change as a result of short‐term temperature fluctuations, but the longer‐term impacts of temperature change remain poorly understood. Here, we investigate temperate reef fishes and mobile invertebrates along Tasmania's east coast, contrasting trends in species richness, abundance, and community structure across seasons within a year to those observed over three decades of warming. Fishes exhibited dynamic seasonal shifts, but interannual changes in richness and abundance balanced out over decades with limited overall net change. In contrast, invertebrate communities changed little seasonally but suffered significant long‐term losses. Our study revealed short‐term ecological changes driven by temperature to be incongruent with long‐term shifts. Species responded in varying ways, depending on life history and ecology. Fishes apparently tracked short temperature pulses, while less mobile invertebrates, such as echinoderms and molluscs, tolerated short‐term fluctuations but exhibited long‐term decline. Multi‐scale studies across a broad range of taxa are needed to clarify thermal responses. The most vulnerable taxa—those facing long‐term thermal stress—may be overlooked through decisions based on short‐term studies, risking major biodiversity loss.

A list of eclectic viruses, virus-like diseases and viroids of grapevines that should not be considered for regulatory oversight: a global plea from virologists - Marc Fuchs; Maher Al Rwahnih; Arnaud G. Blouin; Johan Burger; Kar Mun Chooi; Fiona Constable; Filiz Ertunc; Nicola Fiore; Nuredin Habili; Jean-Michel Hily; Nikolaos Katis; Olivier Lemaire; et al. (Journal of Plant Pathology, 2025)
Grapevine ( Vitis spp.) propagation material is profusely exchanged across geographic and regulatory boundaries. Trading germplasm increases the diversity of cultivars and rootstocks with enhanced viticultural attributes but also risks the dissemination of pests and detrimental pathogens such as viruses in new grape production areas. Therefore, regulations are established to facilitate the safe trade of Vitis propagation material with desirable traits. Regrettably regulations are sometimes inadequate. Consequently, the accessibility of desired germplasm for growers might be unduly delayed, providing opportunities to circumvent regulations by illegally introducing germplasm of interest, amidst risking epidemics of viruses of concern, including quarantined agents, and jeopardizing the health of vineyards. To address some of the regulatory limitations, scientists from around the world recently defined phantom agents in fruit crops, including grapevines, and provided a compelling case for their exclusion from regulatory oversight. Simultaneously, a group of virologists realized the need to complement the list of phantom agents in grapevines by considering additional viruses, virus-like diseases and viroids that should not be subject to regulatory oversight. Here, we present a list of nine viruses, 14 virus-like diseases, nine viroids, and 129 presumed viruses of the grapevine, that are not phantom agents but should be excluded from regulation or should not be regulated. Our list is anticipated to assist policy makers adopt regulations that expedite the safe exchange of Vitis germplasm across regulatory boundaries while reducing incentives for illicit introductions.

Untangling the Complexity of Climate Change Effects on Plant Reproductive Traits and Pollinators: A Systematic Global Synthesis - Silvana Martén‐Rodríguez; Edson Jacob Cristobal‐Pérez; Martín Hesajim de Santiago‐Hernández; Guillermo Huerta‐Ramos; Lucero Clemente‐Martínez; Gary Krupnick; Orley Taylor; Martha Lopezaraiza‐Mikel; Francisco Javier Balvino‐Olvera; Eugenia M. Sentíes‐Aguilar; Sergio Díaz‐Infante; Armando Aguirre Jaimes; et al. (Global Change Biology, 2025)
Climate change is expected to affect the morphological, physiological, and life‐history traits of plants and animal pollinators due to more frequent extreme heat and other altered weather patterns. This systematic literature review evaluates the effects of climate change on plant and pollinator traits on a global scale to determine how species responses vary among Earth's ecosystems, climate variables, taxonomic groups, and organismal traits. We compiled studies conducted under natural or experimental conditions (excluding agricultural species) and analyzed species response patterns for each trait (advance vs. delay or no change for phenology, decrease vs. increase or no change for other traits). Climate change has advanced plant and animal phenologies across most Earth's biomes, but evidence for temporal plant–pollinator mismatches remains limited. Flower production and plant reproductive success showed diverse responses to warming and low water availability in Alpine and Temperate ecosystems, and a trend for increased or neutral responses in Arctic and Tropical biomes. Nectar rewards mainly experienced negative effects under warming and drought across Alpine and Temperate biomes, but scent emissions increased or changed in composition. Life form (woody vs. nonwoody species) did not significantly influence trait response patterns to climate change. Pollinator fecundity, size, life‐history, developmental, and physiological traits mostly declined with warming across biomes; however, animal abundance and resource acquisition traits showed diverse responses. This review identified critical knowledge gaps that limit our understanding of the impacts of climate change, particularly in tropical/subtropical biomes and southern latitudes. It also highlights the urgent need to sample across a greater range of plant families and pollinator taxa (e.g., beetles, wasps, vertebrates). The diversity of climate change effects should be assessed in the context of other anthropogenic drivers of global change that threaten critically important pollination interactions.

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Methane flux from Beringian coastal wetlands for the past 20,000 years - Matthias Fuchs; Miriam C. Jones; Evan J. Gowan; Steve Frolking; Katey Walter Anthony; Guido Grosse; Benjamin M. Jones; Jonathan A. O'Donnell; Laura Brosius; Claire Treat (Quaternary Science Reviews, 2024)

Multirotor UAV icing correlated to liquid water content measurements in natural supercooled clouds - Anna J. Miller; Christopher Fuchs; Nadja Omanovic; Fabiola Ramelli; Patric Seifert; Robert Spirig; Huiying Zhang; Emilie Fons; Ulrike Lohmann; Jan Henneberger (Cold Regions Science and Technology, 2024)

Hybridization and reticulate evolution in Diphasiastrum (flat-branched clubmosses, Lycopodiaceae) – New data from the island of Taiwan and Vietnam - M. Schnittler; M. Inoue; O.N. Shchepin; J. Fuchs; H. Chang; P. Lamkowski; R. Knapp; K. Horn; H.W. Bennert; M. Bog (Molecular Phylogenetics and Evolution, 2024)

Impacts of irregularly-distributed acidified brine flow on geo-chemo-mechanical alteration in an artificial shale fracture under differential stress - Samantha J. Fuchs; Dustin Crandall; Johnathan E. Moore; Mayandi Sivaguru; Bruce W. Fouke; D. Nicolas Espinoza; Ange-Therese Akono; Charles J. Werth (International Journal of Greenhouse Gas Control, 2024)

Does ‘portion size’ matter? Brain responses to food and non-food cues presented in varying amounts - Bari A. Fuchs; Alaina L. Pearce; Barbara J. Rolls; Stephen J. Wilson; Emma Jane Rose; Charles F. Geier; Kathleen L. Keller (Appetite, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Investigation on the thermal budget and flow field of a manikin and comparison with human subject in different scenarios - Abhilash Sankaran; Rainer Hain; Christina Matheis; Thomas Fuchs; Victor Norrefeldt; Gunnar Grün; Christian J. Kähler (Building and Environment, 2024)

Identifying Key Plant Traits and Ecosystem Properties Affecting Wave Attenuation and the Soil Organic Carbon Content in Tidal Marshes - Tilla Schulte Ostermann; Maike Heuner; Elmar Fuchs; Stijn Temmerman; Ken Schoutens; Tjeerd J. Bouma; Vanessa Minden (Estuaries and Coasts, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Differential Flight Capacity of Spissistilus festinus (Hemiptera: Membracidae) by Sex and Age - Carlos A. Antolínez; Mason Chandler; Victoria Hoyle; Marc Fuchs; Monique J. Rivera (Journal of Insect Behavior, 2023)

Large inter-annual variation in carbon sink strength of a permanent grassland over 16 years: Impacts of management practices and climate - Iris Feigenwinter; Lukas Hörtnagl; Matthias J. Zeeman; Werner Eugster; Kathrin Fuchs; Lutz Merbold; Nina Buchmann (Agricultural and Forest Meteorology, 2023)

Children with lower ratings of executive functions have a greater response to the portion size effect - Kathleen L. Keller; Alaina L. Pearce; Bari Fuchs; Kyle Hallisky; Barbara J. Rolls; Stephen J. Wilson; Charles Geier; Emma J. Rose (Appetite, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Thermal and behavioural responses of moose to chemical immobilisation from a helicopter - Anne Randi Græsli; Alexandra Thiel; Larissa T. Beumer; Boris Fuchs; Fredrik Stenbacka; Wiebke Neumann; Navinder J. Singh; Göran Ericsson; Jon M. Arnemo; Alina L. Evans (European Journal of Wildlife Research, 2023)
Instrumentation and sample collection for wildlife research and management may require chemical immobilisation of animals, which may entail physiological and behavioural effects on them. It is therefore important to evaluate the immobilisation protocols to reduce the risk of mortality and morbidity of the handled animals and their populations. Using a multi-sensor approach, we assessed the short-term (< 10 days) thermal and behavioural responses of 10 adult female moose ( Alces alces ) equipped with ruminal temperature loggers and GPS collars with accelerometers to helicopter-based chemical immobilisations. We investigated the body temperature ( T b ), movement rates, and resting time before, during, and after recapture. Chemical immobilisations on average increased maximum T b by 0.71 °C during the capture day, and imposed longer travel distances during the capture day and the two following days (3.8 and 1.8 km, respectively), compared to a 10-day reference period before the immobilisation. The probability of resting was 5–6% lower on the capture day and the two following days compared to the reference period, and females with offspring had a higher probability of resting than females without. Maximum T b , movement rate, and resting time returned to pre-capture levels on an individual level 2 h, 3 days, and 3 days after the immobilisation, respectively. Chemical immobilisation of moose from a helicopter increases the energy expenditure deduced through movement and T b rise lasting for hours to days. Ecological and physiological studies aimed at inferring general patterns may encounter bias if including sensor and tracking data from tagged animals without accounting for potential post-capture effects.

Influences of brood-dependent behavioral variation on blue crab (Callinectes sapidus) larval transport in a wind-driven estuarine plume - Joseph C. Caracappa; Daphne M. Munroe; Heidi L. Fuchs; Robert J. Chant (Ecological Modelling, 2023)

Determining seasonal recharge, storage changes, and specific yield using repeat microgravity and water-level measurements in the Mesilla Basin alluvial aquifer, New Mexico, 2016–2018 - Andrew J. Robertson; Jeffrey R. Kennedy; Libby M. Wildermuth; Meghan T. Bell; Erek H. Fuchs; Alex Rinehart; Irene Fernald (Journal of Applied Geophysics, 2023)

Lipid droplets and perilipins in canine osteosarcoma. Investigations on tumor tissue, 2D and 3D cell culture models - N. Leitner; J. Hlavatý; R. Ertl; S. Gabner; A. Fuchs-Baumgartinger; Ingrid Walter (Veterinary Research Communications, 2022)
Lipid droplets were identified as important players in biological processes of various tumor types. With emphasis on lipid droplet-coating proteins (perilipins, PLINs), this study intended to shed light on the presence and formation of lipid droplets in canine osteosarcoma. For this purpose, canine osteosarcoma tissue samples ( n = 11) were analyzed via immunohistochemistry and electron microscopy for lipid droplets and lipid droplet-coating proteins (PLINs). Additionally, we used the canine osteosarcoma cell lines D-17 and COS4288 in 2D monolayer and 3D spheroid (cultivated for 7, 14, and 21 days) in vitro models, and further analyzed the samples by means of histochemistry, immunofluorescence, molecular biological techniques (RT-qPCR, Western Blot) and electron microscopical imaging. Lipid droplets, PLIN2, and PLIN3 were detected in osteosarcoma tissue samples as well as in 2D and 3D cultivated D-17 and COS4288 cells. In spheroids, specific distribution patterns of lipid droplets and perilipins were identified, taking into consideration cell line specific zonal apportionment. Upon external lipid supplementation (oleic acid), a rise of lipid droplet amount accompanied with an increase of PLIN2 expression was observed. Detailed electron microscopical analyzes revealed that lipid droplet sizes in tumor tissue were comparable to that of 3D spheroid models. Moreover, the biggest lipid droplets were found in the central zone of the spheroids at all sampling time-points, reaching their maximum size at 21 days. Thus, the 3D spheroids can be considered as a relevant in vitro model for further studies focusing on lipid droplets biology and function in osteosarcoma.

Characterizing U.S. drought over the past 20 years using the U.S. drought monitor - Ronald D. Leeper; Rocky Bilotta; Bryan Petersen; Crystal J. Stiles; Richard Heim; Brian Fuchs; Olivier P. Prat; Michael Palecki; Steve Ansari (International Journal of Climatology, 2022)
The main challenge of evaluating droughts in the context of climate change and linking these droughts to adverse societal outcomes is a lack of a uniform definition that identifies drought conditions at a location and time. The U.S. Drought Monitor (USDM), created in 1999, is a well‐established composite index that combines drought indicators across the hydrological cycle (i.e., meteorological to hydrological) with information from local experts. This makes the USDM one of the most holistic measures for evaluating past drought conditions across the United States. In this study, the USDM was used to define drought events as consecutive periods in time where the USDM status met or exceeded D1 conditions over the past 20 years. This analysis was applied to 5 km grid cells covering the U.S. and Puerto Rico to characterize the frequency, duration, and intensification rates of drought, and the timing of onset, amelioration, and other measures for every drought event on record. Results from this analysis revealed stark contrasts in the evolution of drought across the United States. Over the western United States, droughts evolved much slower, resulting in longer‐lasting but fewer droughts. The eastern United States experienced more frequent, shorter‐duration events. Given the slower evolution from onset to drought peak, flash droughts, which made up 9.8% of all droughts, were less common across the western United States, with a greater frequency over the southern United States. The most severe drought event on record was the 2012 drought, when more than 21% of the United States experienced its largest number of weeks at or above extreme (D3) drought conditions. The availability of historical drought events would support future societal impacts studies relating drought to adverse outcomes and aid in the evaluation of mitigation strategies by providing a dataset to local decision makers to compare and evaluate past droughts.

Estuarine retention of larvae: Contrasting effects of behavioral responses to turbulence and waves - Jessica C. Garwood; Heidi L. Fuchs; Gregory P. Gerbi; Elias J. Hunter; Robert J. Chant; John L. Wilkin (Limnology and Oceanography, 2022)
The intensity of small‐scale fluid motions varies among coastal seascapes, which could drive species‐specific behavioral adaptations in planktonic larvae. For example, inlets and estuaries typically have stronger turbulence and weaker surface gravity waves than the continental shelf. In the Mid‐Atlantic Bight, eastern mudsnails ( Ilyanassa obsoleta ) inhabit inlets and estuaries, whereas threeline mudsnails ( Ilyanassa trivittata ) inhabit the continental shelf. The two species' larvae respond differently to hydrodynamic signals: both hover in calm conditions and sink in response to vorticity, a signal of turbulence, while only shelf snail larvae also sink and swim up in response to accelerations, which can be large under waves. We investigated how these observed larval behaviors and more idealized ones affect retention and settlement in estuaries using numerical experiments. Virtual larvae were released and tracked in a regional model of Delaware Bay and the adjacent shelf. Behaviors that involved downward motions, including vorticity‐induced behaviors, helped concentrate larvae near the bottom and enhanced retention in the bay. In contrast, behaviors that involved upward motions, including acceleration‐induced behaviors, promoted export onto the shelf. Compared to neutral buoyancy, the vorticity‐induced behaviors also conferred longer residence times in the bay, higher settlement probabilities, and shorter pelagic larval durations, all of which would be advantageous to estuarine species. This integration of larval observations with simulations provides evidence that behavioral responses to coastal physics can reduce larval mortality by enhancing retention and settlement in native seascapes.

Pentalinonsterol, a Phytosterol from Pentalinon andrieuxii, is Immunomodulatory through Phospholipase A2 in Macrophages toward its Antileishmanial Action - Sanjay Varikuti; Andrew B. Shelton; Sainath R. Kotha; Travis Gurney; Gaurav Gupta; Thomas J. Hund; James R. Fuchs; A. Douglas Kinghorn; Nidhi Srivastava; Abhay R. Satoskar; Narasimham L. Parinandi (Cell Biochemistry and Biophysics, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Degrading permafrost river catchments and their impact on Arctic Ocean nearshore processes - Paul J. Mann; Jens Strauss; Juri Palmtag; Kelsey Dowdy; Olga Ogneva; Matthias Fuchs; Michael Bedington; Ricardo Torres; Luca Polimene; Paul Overduin; Gesine Mollenhauer; Guido Grosse; et al. (Ambio, 2022)
Arctic warming is causing ancient perennially frozen ground (permafrost) to thaw, resulting in ground collapse, and reshaping of landscapes. This threatens Arctic peoples' infrastructure, cultural sites, and land-based natural resources. Terrestrial permafrost thaw and ongoing intensification of hydrological cycles also enhance the amount and alter the type of organic carbon (OC) delivered from land to Arctic nearshore environments. These changes may affect coastal processes, food web dynamics and marine resources on which many traditional ways of life rely. Here, we examine how future projected increases in runoff and permafrost thaw from two permafrost-dominated Siberian watersheds—the Kolyma and Lena, may alter carbon turnover rates and OC distributions through river networks. We demonstrate that the unique composition of terrestrial permafrost-derived OC can cause significant increases to aquatic carbon degradation rates (20 to 60% faster rates with 1% permafrost OC). We compile results on aquatic OC degradation and examine how strengthening Arctic hydrological cycles may increase the connectivity between terrestrial landscapes and receiving nearshore ecosystems, with potential ramifications for coastal carbon budgets and ecosystem structure. To address the future challenges Arctic coastal communities will face, we argue that it will become essential to consider how nearshore ecosystems will respond to changing coastal inputs and identify how these may affect the resiliency and availability of essential food resources.

A draft genome assembly of “Cas” (Psidium friedrichsthalianum (O. Berg) Nied.): an indigenous crop of Costa Rica untapped - Mónica Rojas-Gómez; Jose Pablo Jiménez-Madrigal; Maripaz Montero-Vargas; Randall Loaiza-Montoya; Max Chavarría; Esteban Meneses; Eric J. Fuchs (Genetic Resources and Crop Evolution, 2022)

Metagenomic analysis of nepoviruses: diversity, evolution and identification of a genome region in members of subgroup A that appears to be important for host range - J. M. Hily; N. Poulicard; J. Kubina; J. S. Reynard; A. S. Spilmont; M. Fuchs; O. Lemaire; E. Vigne (Archives of Virology, 2021)
Data mining and metagenomic analysis of 277 open reading frame sequences of bipartite RNA viruses of the genus Nepovirus , family Secoviridae , were performed, documenting how challenging it can be to unequivocally assign a virus to a particular species, especially those in subgroups A and C, based on some of the currently adopted taxonomic demarcation criteria. This work suggests a possible need for their amendment to accommodate pangenome information. In addition, we revealed a host-dependent structure of arabis mosaic virus (ArMV) populations at a cladistic level and confirmed a phylogeographic structure of grapevine fanleaf virus (GFLV) populations. We also identified new putative recombination events in members of subgroups A, B and C. The evolutionary specificity of some capsid regions of ArMV and GFLV that were described previously and biologically validated as determinants of nematode transmission was circumscribed in silico . Furthermore, a C-terminal segment of the RNA-dependent RNA polymerase of members of subgroup A was predicted to be a putative host range determinant based on statistically supported higher π (substitutions per site) values for GFLV and ArMV isolates infecting Vitis spp. compared with non- Vitis -infecting ArMV isolates. This study illustrates how sequence information obtained via high-throughput sequencing can increase our understanding of mechanisms that modulate virus diversity and evolution and create new opportunities for advancing studies on the biology of economically important plant viruses.

Endogenous anandamide and self-reported pain are significantly reduced after a 2-week multimodal treatment with and without radon therapy in patients with knee osteoarthritis: a pilot study - M. Gaisberger; J. Fuchs; M. Riedl; S. Edtinger; R. Reischl; G. Grasmann; B. Hölzl; F. Landauer; H. Dobias; F. Eckstein; M. Offenbächer; M. Ritter; et al. (International Journal of Biometeorology, 2021)
Multimodal therapies comprising spa applications are widely used as non-pharmaceutical treatment options for musculoskeletal diseases. The purpose of this randomized, controlled, open pilot study was to elucidate the involvement of the endocannabinoid system in a multimodal therapy approach. Twenty-five elderly patients with knee osteoarthritis (OA) received a 2-week spa therapy with or without combination of low-dose radon therapy in the Bad Gastein radon gallery. A 10-point numerical rating scale (pain in motion and at rest), WOMAC questionnaire, and the EuroQol-5D (EQ-5D) questionnaire were recorded at baseline, and during treatment period at weeks one and two, and at 3-month and 6-month follow-ups. Plasma levels of the endocannabinoid anandamide (AEA) were determined at baseline and at 2 weeks, and serum levels of several cartilage metabolism markers at all five time-points. A significant and sustained reduction of self-reported knee pain was observed in the study population, but no further significant effect of the additional radon therapy up and above base therapy. This pain reduction was accompanied by a significant reduction of AEA plasma levels during treatment in both groups. No significant differences were seen in serum marker concentrations between the groups treated with or without radon, but a small reduction of serum cartilage degradation markers was observed during treatment in both groups. This is the first study investigating AEA levels in the context of a non-pharmacological OA treatment. Since the endocannabinoid system represents a potential target for the development of new therapeutics, further studies will have to elucidate its involvement in OA pain.

Missense and truncating variants in CHD5 in a dominant neurodevelopmental disorder with intellectual disability, behavioral disturbances, and epilepsy - Ilaria Parenti; Daphné Lehalle; Caroline Nava; Erin Torti; Elsa Leitão; Richard Person; Takeshi Mizuguchi; Naomichi Matsumoto; Mitsuhiro Kato; Kazuyuki Nakamura; Stella A. de Man; Heidi Cope; et al. (Human Genetics, 2021)
Located in the critical 1p36 microdeletion region, the chromodomain helicase DNA-binding protein 5 ( CHD5 ) gene encodes a subunit of the nucleosome remodeling and deacetylation (NuRD) complex required for neuronal development. Pathogenic variants in six of nine chromodomain (CHD) genes cause autosomal dominant neurodevelopmental disorders, while CHD5 -related disorders are still unknown. Thanks to GeneMatcher and international collaborations, we assembled a cohort of 16 unrelated individuals harboring heterozygous CHD5 variants, all identified by exome sequencing. Twelve patients had de novo CHD5 variants, including ten missense and two splice site variants. Three familial cases had nonsense or missense variants segregating with speech delay, learning disabilities, and/or craniosynostosis. One patient carried a frameshift variant of unknown inheritance due to unavailability of the father. The most common clinical features included language deficits (81%), behavioral symptoms (69%), intellectual disability (64%), epilepsy (62%), and motor delay (56%). Epilepsy types were variable, with West syndrome observed in three patients, generalized tonic–clonic seizures in two, and other subtypes observed in one individual each. Our findings suggest that, in line with other CHD-related disorders, heterozygous CHD5 variants are associated with a variable neurodevelopmental syndrome that includes intellectual disability with speech delay, epilepsy, and behavioral problems as main features.

Full Parameterisation Matters for the Best Performance of Crop Models: Inter-comparison of a Simple and a Detailed Maize Model - A. M. Manschadi; J. Eitzinger; M. Breisch; W. Fuchs; T. Neubauer; A. Soltani (International Journal of Plant Production, 2021)
Process-based crop growth models have become indispensable tools for investigating the effects of genetic, management, and environmental factors on crop productivity. One source of uncertainty in crop model predictions is model parameterization, i.e. estimating the values of model input parameters, which is carried out very differently by crop modellers. One simple (SSM-iCrop) and one detailed (APSIM) maize ( Zea mays L.) model were partially or fully parameterized using observed data from a 2-year field experiment conducted in 2016 and 2017 at the UFT (Universitäts- und Forschungszentrum Tulln, BOKU) in Austria. Model initialisation was identical for both models based on field measurements. Partial parameterization (ParLevel_1) was first performed by estimating only those parameters related to crop phenology. Full parameterization (ParLevel_2) was then conducted by estimating parameters related to phenology plus those affecting dry mass production and partitioning, nitrogen uptake, and grain yield formation. With ParLevel_1, both models failed to provide accurate estimation of LAI, dry mass accumulation, nitrogen uptake and grain yield, but the performance of APSIM was generally better than SSM-iCrop. Full parameterization greatly improved the performance of both crop models, but it was more effective for the simple model, so that SSM-iCrop was equally well or even better compared to APSIM. It was concluded that full parameterization is indispensable for improving the accuracy of crop model predictions regardless whether they are simple or detailed. Simple models seem to be more vulnerable to incomplete parameterization, but they better respond to full parameterization. This needs confirmation by further research.

Tryptophan depletion predicts lower positive affect in sexual minority men living with HIV who use methamphetamine - Ji-Young Lee; Tiffany R. Glynn; Judith T. Moskowitz; Dietmar Fuchs; Torsten B. Neilands; Samantha E. Dilworth; Daniel J. Feaster; Allan Rodriguez; Adam W. Carrico (Journal of NeuroVirology, 2021)

Isolation and characterization of microsatellites for the neotropical dioecious palm Chamaedorea tepejilote (Arecaceae) and cross-amplification in other Chamaedorea species - Eric J. Fuchs; Alfredo Cascante-Marin; Ruth Madrigal-Brenes; Nick Harvey; Mauricio Quesada (Molecular Biology Reports, 2020)

Correction to: Believing is seeing: lessons from emerging viruses in grapevine - Elizabeth J. Cieniewicz; Wenping Qiu; Pasquale Saldarelli; Marc Fuchs (Journal of Plant Pathology, 2020)

Believing is seeing: lessons from emerging viruses in grapevine - Elizabeth J. Cieniewicz; Wenping Qiu; Pasquale Saldarelli; Marc Fuchs (Journal of Plant Pathology, 2020)

Journal Club - Wolfgang Wohlleben; Jochen Graw; Roland Benz; Johannes Sander; Jonathan Wolf Mueller; Christoph von Ballmoos; Miriam Herbert; Daniela Kruck; Martin Thanbichler; Gottfried Wilharm; Kai Thormann; Thilo M. Fuchs; et al. (BIOspektrum, 2020)

Evaluation of the therapeutic potential of the selective p38 MAPK inhibitor Skepinone-L and the dual p38/JNK 3 inhibitor LN 950 in experimental K/BxN serum transfer arthritis - Philipp Guenthoer; Kerstin Fuchs; Gerald Reischl; Leticia Quintanilla-Martinez; Irene Gonzalez-Menendez; Stefan Laufer; Bernd J. Pichler; Manfred Kneilling (Inflammopharmacology, 2019)

MDH1 deficiency is a metabolic disorder of the malate–aspartate shuttle associated with early onset severe encephalopathy - Melissa H. Broeks; Hanan E. Shamseldin; Amal Alhashem; Mais Hashem; Firdous Abdulwahab; Tarfa Alshedi; Iman Alobaid; Fried Zwartkruis; Denise Westland; Sabine Fuchs; Nanda M. Verhoeven-Duif; Judith J. M. Jans; et al. (Human Genetics, 2019)

Dynamic interactions between plant viruses and their hosts for symptom development - Larissa J. Osterbaan; Marc Fuchs (Journal of Plant Pathology, 2019)

Isolation and characterization of microsatellites loci in Spondias purpurea (Anacardiaceae) and cross amplification in congeneric species - E. Jacob Cristóbal-Pérez; Eric J. Fuchs; Nick Harvey; Mauricio Quesada (Molecular Biology Reports, 2019)

Gene flow and genetic admixture across a secondary contact zone between two divergent lineages of the Eurasian Green Woodpecker Picus viridis - J.-M. Pons; C. Masson; G. Olioso; J. Fuchs (Journal of Ornithology, 2019)

Habitat fragmentation reduces plant progeny quality: a global synthesis - Ramiro Aguilar; Edson Jacob Cristóbal‐Pérez; Francisco Javier Balvino‐Olvera; María de Jesús Aguilar‐Aguilar; Natalia Aguirre‐Acosta; Lorena Ashworth; Jorge A. Lobo; Silvana Martén‐Rodríguez; Eric J. Fuchs; Gumersindo Sanchez‐Montoya; Gabriel Bernardello; Mauricio Quesada (Ecology Letters, 2019)
Most of the world's land surface is currently under human use and natural habitats remain as fragmented samples of the original landscapes. Measuring the quality of plant progeny sired in these pervasive environments represents a fundamental endeavour for predicting the evolutionary potential of plant populations remaining in fragmented habitats and thus their ability to adapt to changing environments. By means of hierarchical and phylogenetically independent meta‐analyses we reviewed habitat fragmentation effects on the genetic and biological characteristics of progenies across 179 plant species. Progeny sired in fragmented habitats showed overall genetic erosion in contrast with progeny sired in continuous habitats, with the exception of plants pollinated by vertebrates. Similarly, plant progeny in fragmented habitats showed reduced germination, survival and growth. Habitat fragmentation had stronger negative effects on the progeny vigour of outcrossing‐ than mixed‐mating plant species, except for vertebrate‐pollinated species. Finally, we observed that increased inbreeding coefficients due to fragmentation correlated negatively with progeny vigour. Our findings reveal a gloomy future for angiosperms remaining in fragmented habitats as fewer sired progeny of lower quality may decrease recruitment of plant populations, thereby increasing their probability of extinction.

Modeling $$\hbox {CO}_2$$-Induced Alterations in Mt. Simon Sandstone via Nanomechanics - Ange-Therese Akono; Pooyan Kabir; Zhuofan Shi; Samantha Fuchs; Theodore T. Tsotsis; Kristian Jessen; Charles J. Werth (Rock Mechanics and Rock Engineering, 2019)

Characteristics of meiofauna in extreme marine ecosystems: a review - Daniela Zeppilli; Daniel Leduc; Christophe Fontanier; Diego Fontaneto; Sandra Fuchs; Andrew J. Gooday; Aurélie Goineau; Jeroen Ingels; Viatcheslav N. Ivanenko; Reinhardt Møbjerg Kristensen; Ricardo Cardoso Neves; Nuria Sanchez; et al. (Marine Biodiversity, 2018)

Influence of immunostimulant polysaccharides, nucleic acids, and Bacillus strains on the innate immune and acute stress response in turbots (Scophthalmus maximus) fed soy bean- and wheat-based diets - V. I. Fuchs; J. Schmidt; M. J. Slater; B. H. Buck; D. Steinhagen (Fish Physiology and Biochemistry, 2017)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Paleolimnological features of a mega-lake phase in the Makgadikgadi Basin (Kalahari, Botswana) during Marine Isotope Stage 5 inferred from diatoms - Mareike Schmidt; Markus Fuchs; Andrew C. G. Henderson; Annette Kossler; Melanie J. Leng; Anson W. Mackay; Elisha Shemang; Frank Riedel (Journal of Paleolimnology, 2017)

Complex phylogeographic patterns indicate Central American origin of two widespread Mesoamerican Quercus (Fagaceae) species - Hernando Rodríguez-Correa; Ken Oyama; Mauricio Quesada; Eric J. Fuchs; Maura Quezada; Lilian Ferrufino; Susana Valencia-Ávalos; Alfredo Cascante-Marín; Antonio González-Rodríguez (Tree Genetics & Genomes, 2017)

Enhanced aphid abundance in spring desynchronizes predator–prey and plant–microorganism interactions - Benjamin Fuchs; Tatjana Breuer; Simone Findling; Markus Krischke; Martin J. Mueller; Andrea Holzschuh; Jochen Krauss (Oecologia, 2017)

Land management: data availability and process understanding for global change studies - Karl‐Heinz Erb; Sebastiaan Luyssaert; Patrick Meyfroidt; Julia Pongratz; Axel Don; Silvia Kloster; Tobias Kuemmerle; Tamara Fetzel; Richard Fuchs; Martin Herold; Helmut Haberl; Chris D. Jones; et al. (Global Change Biology, 2017)
In the light of daunting global sustainability challenges such as climate change, biodiversity loss and food security, improving our understanding of the complex dynamics of the Earth system is crucial. However, large knowledge gaps related to the effects of land management persist, in particular those human‐induced changes in terrestrial ecosystems that do not result in land‐cover conversions. Here, we review the current state of knowledge of ten common land management activities for their biogeochemical and biophysical impacts, the level of process understanding and data availability. Our review shows that ca. one‐tenth of the ice‐free land surface is under intense human management, half under medium and one‐fifth under extensive management. Based on our review, we cluster these ten management activities into three groups: (i) management activities for which data sets are available, and for which a good knowledge base exists (cropland harvest and irrigation); (ii) management activities for which sufficient knowledge on biogeochemical and biophysical effects exists but robust global data sets are lacking (forest harvest, tree species selection, grazing and mowing harvest, N fertilization); and (iii) land management practices with severe data gaps concomitant with an unsatisfactory level of process understanding (crop species selection, artificial wetland drainage, tillage and fire management and crop residue management, an element of crop harvest). Although we identify multiple impediments to progress, we conclude that the current status of process understanding and data availability is sufficient to advance with incorporating management in, for example, Earth system or dynamic vegetation models in order to provide a systematic assessment of their role in the Earth system. This review contributes to a strategic prioritization of research efforts across multiple disciplines, including land system research, ecological research and Earth system modelling.

Targeting Nanomedicines to Prostate Cancer: Evaluation of Specificity of Ligands to Two Different Receptors In Vivo - Amanda K. Pearce; Adrian V. Fuchs; Nicholas L. Fletcher; Kristofer J. Thurecht (Pharmaceutical Research, 2016)

Cirrhotic patients have good insight into their daily functional impairment despite prior hepatic encephalopathy: comparison with PROMIS norms - Jasmohan S. Bajaj; Melanie B. White; Ariel B. Unser; Dinesh Ganapathy; Andrew Fagan; Edith A. Gavis; Richard K. Sterling; Douglas M. Heuman; Scott Matherly; Puneet Puri; Arun J. Sanyal; Velimir Luketic; et al. (Metabolic Brain Disease, 2016)

The amino-terminal domain of ORF149 of koi herpesvirus is preferentially targeted by IgM from carp populations surviving infection - F. Torrent; A. Villena; P. A. Lee; W. Fuchs; S. M. Bergmann; J. M. Coll (Archives of Virology, 2016)

Assessing the influence of historic net and gross land changes on the carbon fluxes of Europe - Richard Fuchs; Catharina J. E. Schulp; Geerten M. Hengeveld; Peter H. Verburg; Jan G. P. W. Clevers; Mart‐Jan Schelhaas; Martin Herold (Global Change Biology, 2016)
Legacy effects of land cover/use on carbon fluxes require considering both present and past land cover/use change dynamics. To assess past land use dynamics, model‐based reconstructions of historic land cover/use are needed. Most historic reconstructions consider only the net area difference between two time steps (net changes) instead of accounting for all area gains and losses (gross changes). Studies about the impact of gross and net land change accounting methods on the carbon balance are still lacking. In this study, we assessed historic changes in carbon in soils for five land cover/use types and of carbon in above‐ground biomass of forests. The assessment focused on Europe for the period 1950 to 2010 with decadal time steps at 1‐km spatial resolution using a bookkeeping approach. To assess the implications of gross land change data, we also used net land changes for comparison. Main contributors to carbon sequestration between 1950 and 2010 were afforestation and cropland abandonment leading to 14.6 PgC sequestered carbon (of which 7.6 PgC was in forest biomass). Sequestration was highest for old‐growth forest areas. A sequestration dip was reached during the 1970s due to changes in forest management practices. Main contributors to carbon emissions were deforestation (1.7 PgC) and stable cropland areas on peaty soils (0.8 PgC). In total, net fluxes summed up to 203 TgC yr −1 (98 TgC yr −1 in forest biomass and 105 TgC yr −1 in soils). For areas that were subject to land changes in both reconstructions (35% of total area), the differences in carbon fluxes were about 68%. Overall for Europe the difference between accounting for either gross or net land changes led to 7% difference (up to 11% per decade) in carbon fluxes with systematically higher fluxes for gross land change data.

Evolving inter-regional co-operation in flood risk management: distances and types of partnership approaches in Austria - Thomas A. Thaler; Sally J. Priest; Sven Fuchs (Regional Environmental Change, 2016)

The coordination dynamics of mobile conjugate reinforcement - J. A. Scott Kelso; Armin Fuchs (Biological Cybernetics, 2016)

Dilution cultivation of marine heterotrophic bacteria abundant after a spring phytoplankton bloom in the N orth S ea - Richard L. Hahnke; Christin M. Bennke; Bernhard M. Fuchs; Alexander J. Mann; Erhard Rhiel; Hanno Teeling; Rudolf Amann; Jens Harder (Environmental Microbiology, 2015)
Summary The roles of individual bacterioplankton species in the re‐mineralization of algal biomass are poorly understood. Evidence from molecular data had indicated that a spring diatom bloom in the G erman B ight of the N orth S ea in 2009 was followed by a rapid succession of uncultivated bacterioplankton species, including members of the genera U lvibacter , F ormosa , P olaribacter (class F lavobacteria ) and R einekea (class G ammaproteobacteria) . We isolated strains from the same site during the diatom bloom in spring 2010 using dilution cultivation in an artificial seawater medium with micromolar substrate and nutrient concentrations. Flow cytometry demonstrated growth from single cells to densities of 10 4 –10 6 cells ml –1 and a culturability of 35%. Novel F ormosa , P olaribacter and R einekea strains were isolated and had 16 S r RNA gene sequence identities of > 99.8% with bacterioplankton in spring or summer 2009. Genomes of selected isolates were draft sequenced and used for read recruitment of metagenomes from bacterioplankton in 2009. Metagenome reads covered 93% of a F ormosa clade B , 91% of a R einekea and 74% of a F ormosa clade A genome, applying a ≥ 94.5% nucleotide identity threshold. These novel strains represent abundant bacterioplankton species thriving on coastal phytoplankton blooms in the N orth S ea.

Genetic characterization and barcoding of taxa in the genera Landoltia and Spirodela (Lemnaceae) by three plastidic markers and amplified fragment length polymorphism (AFLP) - Manuela Bog; Ulrich Lautenschlager; Maria F. Landrock; Elias Landolt; Joerg Fuchs; K. Sowjanya Sree; Christoph Oberprieler; Klaus-J. Appenroth (Hydrobiologia, 2015)

Enhancement of functional connectivity, working memory and inhibitory control on multi-modal brain MR imaging with Rifaximin in Cirrhosis: Implications for the gut-liver-brain axis - Vishwadeep Ahluwalia; James B. Wade; Douglas M. Heuman; Thomas A. Hammeke; Arun J. Sanyal; Richard K. Sterling; R. Todd Stravitz; Velimir Luketic; Mohammad S. Siddiqui; Puneet Puri; Michael Fuchs; Micheal J. Lennon; et al. (Metabolic Brain Disease, 2014)

CXCR4 antibody treatment suppresses metastatic spread to the lung of intratibial human osteosarcoma xenografts in mice - Patrick Brennecke; Matthias J. E. Arlt; Carmen Campanile; Knut Husmann; Ana Gvozdenovic; Tiziana Apuzzo; Marcus Thelen; Walter Born; Bruno Fuchs (Clinical & Experimental Metastasis, 2014)

Peramine and Lolitrem B from Endophyte-Grass Associations Cascade Up the Food Chain - Benjamin Fuchs; Markus Krischke; Martin J. Mueller; Jochen Krauss (Journal of Chemical Ecology, 2013)

Holocene river and slope activity in the Visoko Basin, Bosnia‐ H erzegovina – climate and land‐use effects - S. DREIBRODT; C. LUBOS; R. HOFMANN; N. MÜLLER‐SCHEEßEL; I. RICHLING; O. NELLE; M. FUCHS; K. RASSMANN; Z. KUJUNDŽIĆ‐VEJZAGIĆ; H.‐R. BORK; J. MÜLLER (Journal of Quaternary Science, 2013)
Alluvial and colluvial deposits were investigated at prehistoric tells close to the Bosna River. The chronology is based on ten radiocarbon ages, five optically stimulated luminescence ages, and on the archaeological record. Fluvial activity of the Bosna River is indicated by overbank fines [ca. 5000 (±1000) BC , 500 BC until today] and a phase of lateral displacement of the river bed with subsequent channel fills ca. 2000–500 BC . Early Holocene fluvial activity was probably triggered by climatic variability but might have promoted the expansion of Neolithic societies into the Visoko Basin. Mid‐ to late Holocene river activity occurred under increased climatic aridity but coincided with the expansion of prehistoric settlements to a wider area of the river basin on hard rocks in the adjacent mountainous areas. The destruction of the thin soil cover in the mountains is discussed as a probable trigger for enduring subsequent river activity. This is also indicated by a change in the geochemical signature of the alluvial sediments. The proposed mechanism might explain the mid to late Holocene river history in other regions. The potential of geochemical analyses and diachronous high‐resolution archaeological records to make inferences regarding sediment sources and geomorphological processes is demonstrated. Copyright © 2013 John Wiley & Sons, Ltd.

Erratum to: Toxicological profiles of selected synthetic cannabinoids showing high binding affinities to the cannabinoid receptor subtype CB1 - Verena J. Koller; Gerhard J. Zlabinger; Volker Auwärter; Sabine Fuchs; Siegfried Knasmueller (Archives of Toxicology, 2013)

Toxicological profiles of selected synthetic cannabinoids showing high binding affinities to the cannabinoid receptor subtype CB1 - Verena J. Koller; Gerhard J. Zlabinger; Volker Auwärter; Sabine Fuchs; Siegfried Knasmueller (Archives of Toxicology, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Mouse large-scale phenotyping initiatives: overview of the European Mouse Disease Clinic (EUMODIC) and of the Wellcome Trust Sanger Institute Mouse Genetics Project - Abdel Ayadi; Marie-Christine Birling; Joanna Bottomley; James Bussell; Helmut Fuchs; Martin Fray; Valérie Gailus-Durner; Simon Greenaway; Richard Houghton; Natasha Karp; Sophie Leblanc; Christoph Lengger; et al. (Mammalian Genome, 2012)

Plasma folate, methylenetetrahydrofolate reductase (MTHFR), and colorectal cancer risk in three large nested case–control studies - Jung Eun Lee; Esther K. Wei; Charles S. Fuchs; David J. Hunter; I-Min Lee; Jacob Selhub; Meir J. Stampfer; Walter C. Willett; Jing Ma; Edward Giovannucci (Cancer Causes & Control, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Anatomically constrained minimum variance beamforming applied to EEG - Vyacheslav Murzin; Armin Fuchs; J. A. Scott Kelso (Experimental Brain Research, 2011)

Long-term trends in survival of a declining population: the case of the little owl (Athene noctua) in the Netherlands - Pascaline J. Le Gouar; Hans Schekkerman; Henk P. van der Jeugd; Arjan Boele; Ronald van Harxen; Piet Fuchs; Pascal Stroeken; Arie J. van Noordwijk (Oecologia, 2011)

Mating system and pollen flow between remnant populations of the endangered tropical tree, Guaiacum sanctum (Zygophyllaceae) - Eric J. Fuchs; J. L. Hamrick (Conservation Genetics, 2011)

Morphology, testes development and behaviour of unusual triploid males in microchromosome‐carrying clones of Poecilia formosa - D. K. Lamatsch; M. Stöck; R. Fuchs; M. Döbler; R. Wacker; J. Parzefall; I. Schlupp; M. Schartl (Journal of Fish Biology, 2010)
In a microchromosome‐carrying laboratory stock of the normally all‐female Amazon molly Poecilia formosa triploid individuals were obtained, all of which spontaneously developed into males. A comparison of morphology of the external and internal insemination apparatus and the gonads, sperm ploidy and behaviour, to laboratory‐bred F 1 hybrids revealed that the triploid P. formosa males, though producing mostly aneuploid sperm, are partly functional males that differ mainly in sperm maturation and sexual motivation from gonochoristic P. formosa males.

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

High-dose, post-transplantation cyclophosphamide to promote graft-host tolerance after allogeneic hematopoietic stem cell transplantation - Leo Luznik; Ephraim J. Fuchs (Immunologic Research, 2010)

Identifying sites of saccade amplitude plasticity in humans: transfer of adaptation between different types of saccade - J. Johanna Hopp; Albert F. Fuchs (Experimental Brain Research, 2010)

Germline polymorphisms in the one-carbon metabolism pathway and DNA methylation in colorectal cancer - Aditi Hazra; Charles S. Fuchs; Takako Kawasaki; Gregory J. Kirkner; David J. Hunter; Shuji Ogino (Cancer Causes & Control, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Evidence for distinct populations of human Merkel cells - A.-C. Eispert; F. Fuchs; J. M. Brandner; P. Houdek; E. Wladykowski; Ingrid Moll (Histochemistry and Cell Biology, 2009)

Association of the TCF7L2 polymorphism with colorectal cancer and adenoma risk - Aditi Hazra; Charles S. Fuchs; Andrew T. Chan; Edward L. Giovannucci; David J. Hunter (Cancer Causes & Control, 2008)

Phenylacetate Metabolism in Thermophiles: Characterization of Phenylacetate-CoA Ligase, the Initial Enzyme of the Hybrid Pathway in Thermus thermophilus - Tobias J. Erb; Wael Ismail; Georg Fuchs (Current Microbiology, 2008)

Flow cytometric measurements do not reveal different ploidy levels in Minthostachys (Lamiaceae) - A. N. Schmidt-Lebuhn; J. Fuchs; M. Kessler (Plant Systematics and Evolution, 2008)

Das nofdp-IDSS — ein interaktives Planungsinstrument zur Realisierung eines naturverträglichen Schutzes vor Hochwasserschäden - Peter J. Horchler; Elmar Fuchs; Axel Winterscheid; Christoph Hübner; Manfred Ostrowski (WASSERWIRTSCHAFT, 2008)

Improvement and application of the biocontrol fungus Stagonospora convolvuli LA39 formulation for efficient control of Calystegia sepium and Convolvulus arvensis - D. Boss; E. Schläpfer; J. Fuchs; G. Défago; M. Maurhofer (Journal of Plant Diseases and Protection, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Microbial control of phosphate in the nutrient‐depleted North Atlantic subtropical gyre - Mikhail V. Zubkov; Isabelle Mary; E. Malcolm S. Woodward; Phillip E. Warwick; Bernhard M. Fuchs; David J. Scanlan; Peter H. Burkill (Environmental Microbiology, 2007)
Summary Little is known about the dynamics of dissolved phosphate in oligotrophic areas of the world's oceans, where concentrations are typically in the nanomolar range. Here, we have budgeted phosphate uptake by the dominant microbial groups in order to assess the effect of the microbial control of this depleted nutrient in the North Atlantic gyre. Low concentrations (2.2 ± 1.2 nM) and rapid microbial uptake (2.1 ± 2.4 nM day −1 ) of bioavailable phosphate were repeatedly determined in surface waters of the North Atlantic oligotrophic gyre during spring and autumn research cruises, using a radiotracer dilution bioassay technique. Upper estimates of the concentration of bioavailable phosphate were 7–55% of the dissolved mineral phosphate suggesting that a considerable part of the chemically measured nanomolar phosphate was in a form unavailable for direct microbial uptake. A 1:1 relationship ( r 2 = 0.96, P Prochlorococcus phototrophic cyanobacteria, were the two major competing groups for bioavailable phosphate. These heterotrophic bacteria had low nucleic acid content and 60% of them comprised of SAR11 clade cells based on the results of fluorescence in situ hybridization. Each of the two competing bacterial groups was responsible for an average of 45% of the phosphate uptake, while Synechococcus cyanobacteria (7%) and picoplanktonic algae (0.3%) played minor roles in direct phosphate uptake. We have demonstrated that phosphate uptake in the oligotrophic gyre is rapid and dominated by two bacterial groups rather than by algae.

O6-Methylguanine-DNA Methyltransferase Leu84Phe and Ile143Val Polymorphisms and Risk of Colorectal Cancer in the Nurses’ Health Study and Physicians’ Health Study (United States) - Gregory J. Tranah; James Bugni; Edward Giovannucci; Jing Ma; Charles Fuchs; Lisa Hines; Leona Samson; David J. Hunter (Cancer Causes & Control, 2006)

Process metallurgy for high performance materials at RWTH Aachen/Germany - B. Friedrich; R. Fuchs; C. Kräutlein; C. Lochbichler; A. Lützerath; E. Milke; J. C. Stoephasius (BHM Berg- und Hüttenmännische Monatshefte, 2006)

A Prospective Study of Body Mass Index, Hypertension, and Smoking and the Risk of Renal Cell Carcinoma (United States) - Keith T. Flaherty; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Frank E. Speizer; Walter C. Willett; Gary C. Curhan (Cancer Causes & Control, 2005)

Neuromagnetic motor fields accompanying self-paced rhythmic finger movement at different rates - Justine M. Mayville; Armin Fuchs; J. A. Scott Kelso (Experimental Brain Research, 2005)

Chronic psychosocial stress in tree shrews: effect of the substance P (NK1 receptor) antagonist L-760735 and clomipramine on endocrine and behavioral parameters - Marieke G. C. van der Hart; Gabriel de Biurrun; Boldizsár Czéh; Nadia M. J. Rupniak; Johan A. den Boer; Eberhard Fuchs (Psychopharmacology, 2005)

Human papillomavirus-positive tonsillar carcinomas: a different tumor entity? - Jens P. Klussmann; Soenke J. Weissenborn; Ulrike Wieland; Volker Dries; Hans E. Eckel; Herbert J. Pfister; Pawel G. Fuchs (Medical Microbiology and Immunology, 2003)

Effects of Forest Fragmentation and Flowering Phenology on the Reproductive Success and Mating Patterns of the Tropical Dry Forest Tree Pachira quinata - Eric J. Fuchs; Jorge A. Lobo; Mauricio Quesada (Conservation Biology, 2003)
The results of several studies suggest that forest fragmentation affects the mating patterns and reproductive success of tropical tree species by reducing pollinator activity, pollen deposition, and outcrossing levels. The flowering synchrony of trees has also been proposed as an additional factor in controlling fruit set and regulating levels of outcrossing, particularly in disturbed habitats. We examined the effects of forest fragmentation and flowering phenology on the reproductive success and genetic structure of the progeny produced by the tropical tree Pachira quinata . We conducted our study in the dry forest of Costa Rica and compared trees in two density and environmental conditions: ( 1 ) isolated trees separated by 500 m from other adult conspecifics and located in disturbed sites and ( 2 ) trees from continuous populations of groups of 20 or more reproductive individuals per hectare surrounded by undisturbed mature forest. Our study was conducted in the Guanacaste Conservation Area, Costa Rica, and surrounding areas. To evaluate flowering phenology, trees were classified as having synchronous or asynchronous flowering. The phenological stage of individuals was classified according to the proximity of the peak flowering date of each tree with respect to the mean peak flowering of the rest of the population. Six percent of the flowers produced a fruit in trees from continuous populations, whereas in isolated trees only 3% of the flowers did so. Fruit set was not affected by the flowering phenology of trees but was influenced mainly by factors associated with forest fragmentation. Seed production per fruit was not affected by forest fragmentation or flowering phenology. Overall, total fruit production per tree was not affected by forest fragmentation, because isolated trees tended to produce more flowers than trees from continuous populations. Genetic analysis revealed that the progeny of trees from continuous populations experienced lower levels of relatedness, a tendency for higher levels of outcrossing, and/or more sires than isolated trees. Our results suggest that forest fragmentation can have an effect on the mating patterns of P. quinata , reducing the number of outcross sires represented in the progeny of isolated trees.

Aspirin, other NSAIDs, and ovarian cancer risk (United States) - Kathleen M. Fairfield; David J. Hunter; Charles S. Fuchs; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2002)

Investigating the site of human saccadic adaptation with express and targeting saccades - J. Johanna Hopp; Albert F. Fuchs (Experimental Brain Research, 2002)

Effects of Dry Tropical Forest Fragmentation on the Reproductive Success and Genetic Structure of the Tree Samanea saman - Alfredo Cascante; Mauricio Quesada; Jorge J. Lobo; Eric A. Fuchs (Conservation Biology, 2002)
Tropical trees are particularly vulnerable to forest fragmentation because of their low densities, self‐incompatibilty system, and high rates of outbreeding. Forest fragmentation is likely to decrease gene flow, increase endogamy, and eventually produce a high differentiation among remnant populations. Our objectives were to evaluate the effect of forest fragmentation on the reproductive success, progeny vigor, and genetic variation of the tropical dry‐forest tree Samanea saman . We conducted our study in the dry forest of Costa Rica and compared two tree conditions to evaluate forest fragmentation: (1) isolated, individual trees more than 500 m from the nearest conspecific and surrounded by agricultural fields, pastures, or small remnant forest patches and (2) trees in continuous populations of 10 or more individuals per hectare and surrounded by undisturbed forest. We compared the probability of natural pollination, seed production, genetic variation, and progeny vigor of trees in isolation and in continuous populations. The probability of flowers receiving more than 23 pollen tubes at the base of styles (the flowers more likely to produce a mature fruit) was significantly greater for trees in continuous populations (2.1%) than for trees in isolation (0.4%). However, flowers from the two tree conditions received similar pollen loads on their stigmas. Fruits of trees from continuous populations produced similar numbers of seeds as isolated trees did and had a similar probability of seed abortion. The probability of seed predation by bruchid beetles was significantly greater in continuous populations (30%) than in isolated trees (20%). The number of undamaged seeds ( potentially viable) was similar for both tree conditions. A genetic analysis of progeny showed that levels of genetic diversity in trees in isolation and in continuous populations were comparable. The effective self‐fertilization rate and inbreeding coefficient of the progeny were slightly higher for isolated trees than for trees in continuous populations. In addition, there was more genetic similarity in the progeny of isolated trees, within and between fruits. Seeds produced by different fruits within a tree were more likely to be related in an isolated tree than in a tree from continuous populations. Seeds produced by trees from continuous populations were more likely to germinate and to produce greater leaf area and biomass as seedlings than progeny from isolated trees. We concluded that the fragmentation of tropical dry forests affects the genetic variation and vigor of S. saman progeny. Isolated trees showed high reproductive capacity, however, in spite of their habitat condition.

Ecotoxicological Characterization of a Disposal Lagoon from a Munition Plant - J. S. Fuchs; M. L. Oneto; N. B. Casabé; O. Gómez Segura; R. Tarulla; M. Vaccarezza; C. Sánchez-Rivas; E. M. Kesten; E. J. Wood (Bulletin of Environmental Contamination and Toxicology, 2001)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

The clinical-chemical screen in the Munich ENU Mouse Mutagenesis Project: screening for clinically relevant phenotypes - Birgit Rathkolb; Tanja Decker; Edith Fuchs; Dian Soewarto; Christiane Fella; Stephan Heffner; Walter Pargent; Rüdiger Wanke; Rudi Balling; Martin Hrabé de Angelis; Helmut J. Kolb; Eckhard Wolf (Mammalian Genome, 2000)

Debris removal by head-pushing in A. florea Fabr. honeybees - M. Sen Sarma; S. Fuchs; J. Tautz (The Science of Nature, 2000)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Behavioral interactions produced by co-administration of 7-OH-DPAT with cocaine or apomorphine in the rat - Taline V. Khroyan; Rita A. Fuchs; Alex M. Beck; Robert S. Groff; J. L. Neisewander (Psychopharmacology, 1999)

Mössbauer and infrared spectrometry of lizardite- 1T from Monte Fico, Elba - Y. Fuchs; J. Linares; M. Mellini (Physics and Chemistry of Minerals, 1998)

A comparison of sequence resolution on plant chromosomes: PRINS versus FISH - M. Menke; J. Fuchs; I. Schubert (Theoretical and Applied Genetics, 1998)

Esterases of Corbicula fluminea as Biomarkers of Exposure to Organophosphorus Pesticides - S. B. Basack; M. L. Oneto; J. S. Fuchs; E. J. Wood; E. M. Kesten (Bulletin of Environmental Contamination and Toxicology, 1998)

Differential effects of 7-OH-DPAT on amphetamine-induced stereotypy and conditioned place preference - T. V. Khroyan; D. A. Baker; R. A. Fuchs; N. Manders; J. L. Neisewander (Psychopharmacology, 1998)

Sutural mineralization of rat calvaria characterized by atomic-force microscopy and transmission electron microscopy - H.-P. Wiesmann; Lifeng Chi; U. Stratmann; Ulrich Plate; Harald Fuchs; Ulrich Joos; Hans J. Höhling (Cell and Tissue Research, 1998)

Differential induction of enzymes involved in anaerobic metabolism of aromatic compounds in the denitrifying bacterium Thauera aromatica - J. Heider; Matthias Boll; Klaus Breese; Sabine Breinig; Christa Ebenau-Jehle; Ulrich Feil; Nasser Gad'on; Diana Laempe; Birgitta Leuthner; M. El-Said Mohamed; Sabine Schneider; Gerhard Burchhardt; et al. (Archives of Microbiology, 1998)

Predictive validity of the extinction/reinstatement model of drug craving - Rita A. Fuchs; L. T. L. Tran-Nguyen; Sheila E. Specio; Robert S. Groff; J. L. Neisewander (Psychopharmacology, 1998)

Parity and other reproductive factors and risk of adenomatous polyps of the distal colorectum (United States) - Elizabeth A. Platz; Maria Elena Martinez; Francine Grodstein; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Edward Giovannucci (Cancer Causes & Control, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Sequence comparison of the 3′-terminal parts of the RNA of four German isolates of sugarcane mosaic potyvirus (SCMV) - U. Oertel; J. Schubert; E. Fuchs (Archives of Virology, 1997)

Cytogenetics in fruit breeding - localization of ribosomal RNA genes on chromosomes of apple (Malus×domestica Borkh.) - M. Schuster; J. Fuchs; I. Schubert (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Identification and transcriptional analysis of pseudorabies virus UL6 to UL12 genes - J. M. Dijkstra; W. Fuchs; T. C. Mettenleiter; B. G. Klupp (Archives of Virology, 1997)

Coordination dynamics of trajectory formation - J. J. Buchanan; J. A. S. Kelso; A. Fuchs (Biological Cybernetics, 1996)

Extending the HKB model of coordinated movement to oscillators with different eigenfrequencies - A. Fuchs; V. K. Jirsa; H. Haken; J. A. Scott Kelso (Biological Cybernetics, 1996)

Coordination dynamics of trajectory formation - J. J. Buchanan; J. A. S. Kelso; A. Fuchs (Biological Cybernetics, 1995)

Extending the HKB model of coordinated movement to oscillators with different eigenfrequencies - A. Fuchs; V. K. Jirsa; H. Haken; J. A. Scott Kelso (Biological Cybernetics, 1995)

Purification of glutaryl-CoA dehydrogenase from Pseudomonas sp., an enzyme involved in the anaerobic degradation of benzoate - Ulrich Hrtel; Elke Eckel; Jrgen Koch; Georg Fuchs; Dietmar Linder; Wolfgang Buckel (Archives of Microbiology, 1993)

Differential expression of enzyme activities initiating anoxic metabolism of various aromatic compounds via benzoyl-CoA - Werner Dangel; Ruth Brackmann; Achim Lack; Magdy Mohamed; Jrgen Koch; Brigitte Oswald; Birgit Seyfried; Andreas Tschech; Georg Fuchs (Archives of Microbiology, 1991)

Effects of temperature on cadmium toxicity to the green algaScenedesmus acutus. II. Light-limited growth in continuous culture - J. M. van Gemert; H. J. G. ten Hoopen; J. A. Roels; A. Fuchs (Antonie van Leeuwenhoek, 1985)

Effects of temperature on cadmium toxicity to the green algaScenedesmus acutus. I. Development of cadmium tolerance in batch cultures - H. J. G. ten Hoopen; P. J. Nobel; A. Schaap; A. Fuchs; J. A. Roels (Antonie van Leeuwenhoek, 1985)

Bacteria and yeasts as possible candidates for the production of inulinases and levanases - A. Fuchs; J. M. de Bruijn; C. J. Niedeveld (Antonie van Leeuwenhoek, 1985)

Introduction and establishment ofApanteles flavipes [Hym.: Braconidae] onDiatraea saccharalis [Lep.: Pyralidae] in texas - T. W. Fuchs; F. R. Huffman; J. W. Smith (BioControl, 1979)